Study on performance optimization for Chinese speech retrieval - ZHENG Tie-ran; HAN Ji-qing; LI Hai-yang (Tongxin xuebao)
A new unit, named word fragment of language model was proposed to take full advantage of the Chinese linguistic information among adjacent syllables, and an algorithm for word fragment selection was studied.The experimental results show, with the language model based on word fragment, syllable accuracy for recognizer is improved and the speech retrieval system gives better performance than the one with only syllable based model.